Iceland : Improving the Equity and Revenue Productivity of the Icelandic Tax System. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Icelandic government has launched a review of the tax system, with a view to improving its income redistribution, growth orientation, and efficiency features, as well as increasing its revenue mobilization potential. It aims at minimizing detrimental effects on employment and growth, and at removing inconsistencies with international practices. The tax measures will boost the revenue potential in line with the government's objectives while substantially increasing income redistribution. The Icelandic Corporate Index Tax would benefit from adopting financial accounting as the basis to determine taxable income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet